Review: Pengaruh Pemberian Ekstrak Propoelix terhadap Morfologi Motilitas dan Jumlah Sel Spermatozoa Tikus Wistar Jantan yang Diinduksi oleh Monosodium Glutamat: Review: The Effect of Propoelix Extract on Motility Morphology and the number of Spermatozoa Cells of Wistar Rat Induced by Monosodium Glutamate - Rahmah, Windya Nazmatur (Borneo Journal of Medical Laboratory Technology, 2020)
Giving MSG can reduce the morphological quality, motility, and count of spermatozoa. Propoelix extract as an antioxidant is evidently capable of a non-enzymatic radical scavenger. This research aims at evaluating the effect of propoelix extract administration on sperm quality of MSG-induced male Wistar rats. Employing the post the only control group design, 18 rats aged 3 months were divided into 3 random groups, weighing ±250 gram. Propoelix extract was given orally for 21 days and on 22 days, cauda epididymis until the ampulla of vas deferens was cut in a glass jar that has been given 0,5 cc of 0,9% physiological solution. The result of spermatozoa morphology (%) in group K (54,5) group P1 (65) group P2 (76) was significantly higher, p < 0,05. Spermatozoa motility (%) in group K (41.3) group P1 (53.8) group P2 (65.3) were significantly higher, p < 0.05. The number of spermatozoa cells (million/ml) in group K (2.65), group P1 (3.63), group P2 (4.91) was significantly higher, p < 0.05. Conculatition of propoelix extract was able to improve the quality of the morphology, motility, and the count of spermatozoa of MSG-induced male Wistar rats.